AAV gene replacement therapy for treating MPS IIIC: Facilitating bystander effects via EV‐mRNA cargo - Tierra A. Bobo; Michael Robinson; Christopher Tofade; Marina Sokolski‐Papkov; Peter Nichols; Stephen Vorobiov; Haiyan Fu (Journal of Extracellular Vesicles, 2024)
Abstract MPS IIIC is a lysosomal storage disease caused by mutations in heparan‐α‐glucosaminide N‐acetyltransferase (HGSNAT), for which no treatment is available. Because HGSNAT is a trans‐lysosomal‐membrane protein, gene therapy for MPS IIIC needs to transduce as many cells as possible for maximal benefits. All cells continuously release extracellular vesicles (EVs) and communicate by exchanging biomolecules via EV trafficking. To address the unmet need, we developed a rAAV‐hHGSNATEV vector with an EV‐mRNA‐packaging signal in the 3′UTR to facilitate bystander effects, and tested it in an in vitro MPS IIIC model. In human MPS IIIC cells, rAAV‐hHGSNATEV enhanced HGSNAT mRNA and protein expression, EV‐hHGSNAT‐mRNA packaging, and cleared GAG storage. Importantly, incubation with EVs led to hHGSNAT protein expression and GAG contents clearance in recipient MPS IIIC cells. Further, rAAV‐hHGSNATEV transduction led to the reduction of pathological EVs in MPS IIIC cells to normal levels, suggesting broader therapeutic benefits. These data demonstrate that incorporating the EV‐mRNA‐packaging signal into a rAAV‐hHGSNAT vector enhances EV packaging of hHGSNAT‐mRNA, which can be transported to non‐transduced cells and translated into functional rHGSNAT protein, facilitating cross‐correction of disease pathology. This study supports the therapeutic potential of rAAVEV for MPS IIIC, and broad diseases, without having to transduce every cell.